A phase II study of first-line afatinib for patients aged ≥75 years with EGFR mutation-positive advanced non-small cell lung cancer: North East Japan Study Group trial NEJ027 - Yuji Minegishi; Ou Yamaguchi; Shunichi Sugawara; Shoichi Kuyama; Satoshi Watanabe; Kazuhiro Usui; Masahide Mori; Osamu Hataji; Toshihiro Nukiwa; Satoshi Morita; Kunihiko Kobayashi; Akihiko Gemma (BMC Cancer, 2021)
Abstract Background Lung cancer is most common among older individuals. However, polypharmacy and comorbidities, which are also more common in older individuals, can limit treatment options. Previous studies suggest that afatinib can be used safely and effectively in elderly patients. This study investigated the anti-tumour activity and safety profile of first-line afatinib in previously-untreated elderly Japanese patients with EGFR mutation-positive non-small cell lung cancer (NSCLC). Methods This was a single-arm, open-label, phase II study, performed in multiple centres in Japan. Previously untreated patients, aged ≥75 years, with EGFR mutation-positive (Del19 or L858R) advanced NSCLC were treated with afatinib 40 mg until disease progression or unacceptable toxicity. Adverse events (AEs) were managed with protocol-defined dose adjustments. The primary endpoint was objective response rate (ORR) by central review. Results In total, 38 patients received at least one dose of afatinib, and 37 were evaluable for response. Median age was 77.5 years (range 75–91), all patients had an Eastern Cooperative Oncology Group performance status of 0 or 1, and 60.5% had Del19-positive disease. Median follow-up was 838 days. ORR was 75.7% (2 complete responses and 26 partial responses). Median progression-free survival was 14.2 months (95% confidence interval [CI], 9.5–19.0). Median overall survival (OS) was 35.2 months (95% CI, 35.2–not reached); the 2-year OS rate was 78.3%. The most common grade 3/4 treatment-related AEs (TRAEs) were diarrhoea (28.9%), paronychia (23.7%), and rash/acne (15.8%). Dose reductions due to TRAEs were reported in 78.9% of patients, and eight (21.1%) patients discontinued afatinib due to TRAEs. No treatment-related deaths were reported. Conclusion Although dose adjustments were relatively common in this small group of Japanese patients aged ≥75 years with EGFR mutation-positive NSCLC, discontinuation occurred much less frequently, and most patients were able to stay on treatment for well over a year. Further, afatinib was associated with high response rates and prolonged PFS and OS. Trial registration The trial is registered with Japan Registry of Clinical Trials (JRCT) as trial number 031180136 (date of initial registration: 19 February 2019), and the University Hospital Network (UMIN) as trial number 000017877 (date of initial registration: 11 June 2015).